2013
DOI: 10.1097/01.naj.0000438865.22036.15
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nurses’ Intentions to Work During the 2009 Influenza A (H1N1) Pandemic

Abstract: To maintain an adequate nursing workforce during a flu pandemic, employers should ensure that policies and procedures include providing adequate PPE for nurses and safeguarding the health of nurses and their families. The level of perceived threat is likely to affect the proportion of nurses willing to work. Some nurses will not work during a flu pandemic no matter what protections and incentives are offered; efforts intended to force or entice all nurses to work are unlikely to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 28 publications
1
72
1
2
Order By: Relevance
“…Dezzani et al examined potential predictors of nurses' intentions to work during the 2009 in uenza A (H1N1) pandemic where nurses were signi cantly more likely to work if certain incentives were offered (e.g., risk allowance, family protection, priority for vaccination/antiviral treatment). (Martin, Brown, & Reid, 2013) Another study revealed that the most in uential factors that motivated people to work were feeling that they were being protected by their country, local government, and hospital. (Imai, 2020) A possible explanation of this phenomenon is that the vast majority of the nurses who work in Qatar are expatriates and particularly from Asia (El-Jardali et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Dezzani et al examined potential predictors of nurses' intentions to work during the 2009 in uenza A (H1N1) pandemic where nurses were signi cantly more likely to work if certain incentives were offered (e.g., risk allowance, family protection, priority for vaccination/antiviral treatment). (Martin, Brown, & Reid, 2013) Another study revealed that the most in uential factors that motivated people to work were feeling that they were being protected by their country, local government, and hospital. (Imai, 2020) A possible explanation of this phenomenon is that the vast majority of the nurses who work in Qatar are expatriates and particularly from Asia (El-Jardali et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have also noted the importance of resilience and attitudes of health care workers. [23][24][25] These prior studies and the existing literature in risk communication underscore the need to examine communal and social factors in mitigating hospital absenteeism. 26,27 The representativeness of the sample for greater populations may warrant a separate study with a higher sample size and a higher response rate, which may be achieved by a different mode of data collection, such as stratified sampling.…”
Section: Discussionmentioning
confidence: 99%
“…7 We observed some variation in the access to PPE, with the most frequent lack of PPE in eldercare and ambulance service. Not surprisingly, previous studies have shown that nurses were less likely to work during a virus outbreak if they did not have access to adequate PPE 19 and that wearing masks as well as intensive training in the use of PPE were associated with better mental health among healthcare workers. 20 21 In our study, we did not investigate if participants actually used the PPE.…”
Section: Comparison With Previous Findingsmentioning
confidence: 98%